(Indoor) isolation, stress and physical inactivity: vicious circles accelerated by Covid-19? - Burtscher, J.; Burtscher, M.; Millet, G. P. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The Covid-19 epidemic necessitates the application of strict isolation strategies to curb virus spreading. Isolation of individuals in combination with fear of contagion, quarantine and stigma, as well as with potential (mis)information overload ("infodemic")1, however, causes chronic stress and is associated with a burden on mental health, posing risk factors for anxiety and depression. It is well understood that chronic stress is a major modulator of immunity2 and thus directly influences probability of infection.